Eje Cultural del Centro Histórico de LojaPropuesta de intervención urbanoarquitectónica con aplicación de TIC´s - Pullaguari Ochoa, Diana Irene (2018)
Abstract:When determining a Cultural Axis; that is to say, a stretch of city, which links a set of cultural facilities, of worship and public spaces, creates an established image, which seeks the revitalization of the sector; It also seeks to consolidate its activities with the sector and strengthen tourism, through its urban architectural intervention and the dissemination of Cultural Heritage through a technological application. The technological advance applied in mobile devices that have an internet connection has accelerated significantly worldwide; that is why we must think about the possibilities of use in the field of architecture, specifically for the interpretation of the Cultural Heritage of the Historic Center of cities, through the application of Augmented Reality, in mobile devices, allows passers-by to travel historic neuralgic spaces, allows to know, spread the Cultural Heritage and in this way go back in time and admire the changes produced with the passage of it; for this reason an integrative proposal is considered as part of a cultural policy of dissemination and revaluation of the local cultural heritage.